FANCJ helicase controls the balance between short- and long-tract gene conversions between sister chromatids. Issue 15 (7th July 2017) - Nath, Sarmi; Somyajit, Kumar; Mishra, Anup; Scully, Ralph; Nagaraju, Ganesh
Abstract: The FANCJ DNA helicase is linked to hereditary breast and ovarian cancers as well as bone marrow failure disorder Fanconi anemia (FA). Although FANCJ has been implicated in the repair of DNA double-strand breaks (DSBs) by homologous recombination (HR), the molecular mechanism underlying the tumor suppressor functions of FANCJ remains obscure. Here, we demonstrate that FANCJ deficient human and hamster cells exhibit reduction in the overall gene conversions in response to a site-specific chromosomal DSB induced by I-SceI endonuclease. Strikingly, the gene conversion events were biased in favour of long-tract gene conversions in FANCJ depleted cells. The fine regulation of short- (STGC) and long-tract gene conversions (LTGC) by FANCJ was dependent on its interaction with BRCA1 tumor suppressor. Notably, helicase activity of FANCJ was essential for controlling the overall HR and in terminating the extended repair synthesis during sister chromatid recombination (SCR). Moreover, cells expressing FANCJ pathological mutants exhibited defective SCR with an increased frequency of LTGC. These data unravel the novel function of FANCJ helicase in regulating SCR and SCR associated gene amplification/duplications and imply that these functions of FANCJ are crucial for the genome maintenance and tumor suppression.